American coalition building of the US-led security network in the Indo-Pacific: US influence-building measures. - Park, Jae Jeok (Australian Journal of International Affairs, 2025)
The US has been constructing a security network in the Indo-Pacific, composed of US-led alliances and security partnerships. This network is less hierarchical than the hub-and-spoke alliance structure that the US maintained during the Cold War. The article suggests that, akin to the 'connectivity strategy' introduced in this special issue, the US, which once dominated a hierarchical hub-and-spoke system with unquestioned centrality, is now striving to enhance its centrality within the US-led security network. To achieve this, the US has been working to improve its 'closeness', 'betweenness', and 'eigenvalue' centrality, in addition to degree centrality. Furthermore, the article posits that the US adopts 'the strategy of association,' as introduced in this special issue. The US has been at the forefront of regional missile defense, maritime security, and dual-use technology development to foster like-mindedness and build trust among network members, viewing China (and North Korea) as the 'other'. Lastly, the article conceptualises 'security mutuality' by building upon the concept of 'alliance mutuality' proposed by William Tow and Amitav Acharya. It asserts that fostering 'security mutuality' is essential for sustaining US coalitional hegemony.